(untitled) (Bangladesh Journal of Agriculture, 2024)
The blast of rice caused by Pyricularia oryzae fungus plays a vital role in reducing the yield of rice (Oryza sativa L.) in Bangladesh. Rice blast is one of the major constraints on rice productivity in many countries, including Bangladesh. An experiment was conducted from November 2022 to April 2023 at the Biotechnology Division of the Bangladesh Institute of Nuclear Agriculture aimed to developing blast-resistant rice varieties using marker-assisted selection. Three rice varieties were used: BRRI dhan48, BRRI dhan58, and IRBL9-W. SSR markers were employed for F1 confirmation, selecting 14 plants for backcrossing. PCR analysis and gel electrophoresis confirmed F1 plants through polymorphic markers. A total of 97 BC1F1 seeds were produced. The study contributes to developing blast-resistant rice lines, crucial for mitigating yield losses caused by Pyricularia oryzae, addressing a significant threat to rice production in Bangladesh. Bangladesh J. Agri. 2024, 49(1): 41-51